Pengaruh Konsentrasi Giberelin Terhadap Pertumbuhan Tiga Varietas Kacang Kedelai - Harahap, Ariani Syahfitri; Sajar, Suryani; Yani, Windri (JURNAL AGROPLASMA, 2025)
The purpose of this study was to determine the growth of three soybean varieties against gibberellin concentration. The study was conducted in Sampecita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra, which was carried out from November 2024 to January 2025. This study used a factorial Randomized Block Design (RAK) experimental design consisting of 2 treatments, namely varieties (Dering 1, Dega 1 and Devon 1) and gibberellin immersion, namely: 0 ppm, 20 ppm, 40 ppm and 60 ppm which were repeated 3 times. The research data were analyzed and continued with the Duncan's mean difference test (DMRT). The results showed that the growth and production of soybean plants against varieties showed a significant effect on the number of productive branches and no significant effect on the parameters of plant height, number of leaves and root length. In the gibberellin treatment and the interaction of the two showed no significant effect on all parameters. Keywords: concentration, gibberellin, growth, soybean, variety